Neoliberalism and Higher Education in Indonesia (Re-scrutinizing the policy of the Independent Campus) - Andika W Gani; M T Malliongi; M Said Zainuddin (Seminar Nasional LP2M UNM, 2022)
Abstract. This study scrutinizes the policy of the Independent Learning of the Independent Campus (Merdeka Belajar Kampus Merdeka - MBKM) by Ministry of Education and Culture of Republic of Indonesia which tends to serve the global market. The aim is to understand the power relations between ideologies and national elites' interests that are intertwined behind the MBKM policy which allegedly accommodates the interests of neoliberalism and global capitalism. This research used the qualitative method (normative research). The data are collected in two ways: firstly, collecting the education policy of the Indonesian government, especially the MBKM regulation, and other sources that are relevant to the research topic; secondly, deep interviews with education experts and intellectuals who concern with this topic. By using a critical perspective, this study concludes that the basic assumption of the MBKM policy is how that Indonesian higher education can accommodate and be relevant to the global market. Instead of universities in Indonesia playing a role to build the national citizens' character, universities through the MBKM policy are present as an instrument of the market and industries. The implication is that academic development in higher education in the future will only focus on developing applied science disciplines and mechanical skills of human beings, not on developing souls and though Indonesian citizens. Keywords: MBKM, Capitalism, Neoliberalism